2016
DOI: 10.1021/acs.est.6b01697
|View full text |Cite
|
Sign up to set email alerts
|

High Electricity Demand in the Northeast U.S.: PJM Reliability Network and Peaking Unit Impacts on Air Quality

Abstract: On high electricity demand days, when air quality is often poor, regional transmission organizations (RTOs), such as PJM Interconnection, ensure reliability of the grid by employing peak-use electric generating units (EGUs). These "peaking units" are exempt from some federal and state air quality rules. We identify RTO assignment and peaking unit classification for EGUs in the Eastern U.S. and estimate air quality for four emission scenarios with the Community Multiscale Air Quality (CMAQ) model during the Jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Sulfate is traditionally considered dominant in determining absolute ALW mass concentrations in this region, and sulfate mass fraction is highest in summer (Carlton and Turpin, 2013;Gasparini et al, 2006). Similar to other regions of the CONUS, SO 4 2mass concentrations are greatest during summertime Clear Sky conditions due to transport (Parworth et al, 2015), increased rates of photochemistry (Stone et al, 2012), and increased electricity sector emissions during heat waves and stagnation events (Appel et al, 2011;Farkas et al, 2016), which generally occur on sunny days.…”
Section: Case Study: the Mid Southmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfate is traditionally considered dominant in determining absolute ALW mass concentrations in this region, and sulfate mass fraction is highest in summer (Carlton and Turpin, 2013;Gasparini et al, 2006). Similar to other regions of the CONUS, SO 4 2mass concentrations are greatest during summertime Clear Sky conditions due to transport (Parworth et al, 2015), increased rates of photochemistry (Stone et al, 2012), and increased electricity sector emissions during heat waves and stagnation events (Appel et al, 2011;Farkas et al, 2016), which generally occur on sunny days.…”
Section: Case Study: the Mid Southmentioning
confidence: 99%
“…5, Table S5). Higher Clear Sky SO 4 2concentrations during summertime are associated with heat waves and stagnation events, which are characterized by a lack of ventilation in high pressure systems (Jacob and Winner, 2009;Wang and Angell, 1999) and higher electricity demand (Farkas et al, 2016) associated with emissions that form sulfate. TOC mass concentrations are nearly always higher during Clear Sky times than Cloudy (Fig.…”
Section: Hygroscopicity and Chemical Compositionmentioning
confidence: 99%
“…Modeled pollutant concentrations are highly sensitive to lateral chemical boundary conditions (e.g., Tang et al, 2007;Katragkou et al, 2010;Schere et al, 2012), and different assumptions regarding changes in long-range transport have been shown to have a significant impact on future pollutant levels (Nolte et al, 2008;Colette et al, 2013;Pfister et al, 2014;Gonzalez-Abraham et al, 2015;He et al, 2016;Zhang et al, 2016). Several previous studies have also highlighted the importance of rising levels of methane for ozone chemistry (Fiore et al, 2002;West and Fiore, 2005;Nolte et al, 2008). To isolate the effects of climate change on air quality, only the meteorological conditions and the meteorologically dependent emissions that are modeled within CMAQ were modified between the historical and future CMAQ simulations.…”
Section: Chemical Transport Modelmentioning
confidence: 99%
“…To investigate changes over the entire annual cycle, regional monthly box plots of MDA8 O 3 , simulated for the historical period and the RCP8.5 simulation, are compared in While most previous studies of the effect of climate change on O 3 pollution have emphasized the summer, when O 3 concentrations are highest, a few investigators have reported increases during spring and autumn, suggesting a lengthening of the ozone season (Fiore et al, 2002;Nolte et al, 2008;Trail et al, 2014). Clifton et al (2014) have projected a reversal of the O 3 seasonal cycle in the northeastern US by the end of the 21st century, with increased methane levels and decreased NO x levels combining to produce a wintertime maximum in surface O 3 .…”
Section: Ozonementioning
confidence: 99%
“…Sulfate mass concentrations increase by a factor of four from summer to winter. Summertime maxima in sulfate mass concentrations in the Eastern U.S. are driven largely by changing SO 2 emissions related to electricity demand, which peaks in summer on High Electricity Demand Days (HEDD) [50,51]. Temporal variance (σ = 7.4 ”g m −3 ) in ALW for Washington D.C. in 2004 is relatively large and driven primarily by the strong seasonal trend of sulfate ( Figure 3) and not RH.…”
Section: 89mentioning
confidence: 99%